PENGARUH DANA PIHAK KETIGA TERHADAP LOAN TO DEPOSIT RATIO PADA SEKTOR PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2020-2024 - Arifin Arifin; Hafsa Eka Safutri Said (Sigma: Journal of Economic and Business, 2025)
The purpose of this study is to determine and analyze the influence or relationship of Third Party Funds to the Loan to Deposit Ratio in the Banking Sector listed on the Indonesia Stock Exchange for the periode 2020-2024. The method used is quantitative description, sampling is random sampling. By using the smart PLS application version.3.3.3. The results of this study indicate that Third Party Funds have a significant negative effect on the Loan to Deposit Ratio. The low level of third party fund collection, the distribution of credit will be high if the distribution of credit is too high, it will result in high non-performing loans. So the results of this study are too high loan to deposit ratio